2011
DOI: 10.1177/0003122411420817
|View full text |Cite
|
Sign up to set email alerts
|

How General Is Trust in “Most People”? Solving the Radius of Trust Problem

Abstract: Generalized trust has become a paramount topic throughout the social sciences, in its own right and as the key civic component of social capital. To date, cross-national research relies on the standard question: “Generally speaking, would you say that most people can be trusted or that you need to be very careful in dealing with people?” Yet the radius problem—that is, how wide a circle of others respondents imagine as “most people”—makes comparisons between individuals and countries problematic. Until now, mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
563
3
25

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 619 publications
(611 citation statements)
references
References 80 publications
20
563
3
25
Order By: Relevance
“…Both elements are mutually conditional in the sense that they are jointly necessary to obtain the desired outcome (Goertz, 2006;Delhey, Newton & Welzel, 2011). Whereas significant research has previously studied the presence/absence of inter-temporal shifts in civic engagement across Western democracies (Paxton, 1999;Putnam, 2000;Stolle & Hooghe, 2003), similar debates regarding the existence and/or drivers of inter-temporal shifts in the engagement-values relation have been much slower to emerge.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Both elements are mutually conditional in the sense that they are jointly necessary to obtain the desired outcome (Goertz, 2006;Delhey, Newton & Welzel, 2011). Whereas significant research has previously studied the presence/absence of inter-temporal shifts in civic engagement across Western democracies (Paxton, 1999;Putnam, 2000;Stolle & Hooghe, 2003), similar debates regarding the existence and/or drivers of inter-temporal shifts in the engagement-values relation have been much slower to emerge.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Previous studies have shown that the further people move from their immediate circle of friends, colleagues, and neighbour, the more sceptical they are (Delhey et al, 2011;Welch et al, 2007). As stated by Delhey et al (2011), "Differences in trust levels can be interpreted sensibly only when trust radiuses are similar" (p. 789).…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…As stated by Delhey et al (2011), "Differences in trust levels can be interpreted sensibly only when trust radiuses are similar" (p. 789). Unfortunately MHS data do not allow us to control the radius of trust.…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…Trust is often referred to as glue that keeps society together, or in less magical terms, a rational process enabling or supporting cooperation between individuals (Putnam 2000). Social trust is thought to represent a wide variety of interrelated aspects (Delhey et al 2011). First, as traditionally argued by economics, social trust reflects people's experience on how often general others in society can be trusted (Hardin 1993).…”
Section: The Differing Impact Of Social Trustmentioning
confidence: 99%